Uji Aktivitas Antioksidan Ekstrak Buah Semangka (Citrullus lanatus) - Mariani, Sri; Rahman, Nurdin; Supriadi, Supriadi (Jurnal Akademika Kimia, 2018)
The aim of this study is to determine the IC50 extracts values of white peel and flesh of red watermelon, white peel and flesh of yellow watermelon as antioxidants. To determine antioxidant activities DPPH reagent was used and UV-Vis spectrophotometry was used to measure Vitamin C as a positive control measurement. The samples mixed with ethanol in a various concentration of 5, 15, 25 and 35 mg/L. The results showed that the IC50 values for each extract of red watermelon flesh, yellow watermelon flesh, white peel of red watermelon, and white peel of yellow watermelon were 16.619, 16.575, 14.729, and 16.782 mg/L, respectively. Vitamin C as positive control has an IC50 value of 9.526 mg/L. These IC50 values showed that vitamin C had higher antioxidant activity than watermelon extracts, but the extracts of watermelon still categorized in strong natural antioxidants. This study concluded that watermelon is good to be consumed because it is a very strong antioxidant.